Inflammatory Lymphocyte in Cell-Mediated Antibacterial Immunity: Factors Governing the Accumulation of Mediator T Cells in Peritoneal Exudates - North, R. J. (1974)
The lymphocytes which mediate immunity to infection with Listeria monocytogenes in the mouse accumulated in casein-induced peritoneal exudates. They were T cells, as evidenced by their susceptibility to anti-θ serum, but some were also destroyed by anti-immunoglobulin serum. For a given number of cells, exudate cells were at least six times more efficient than spleen cells in protecting normal recipients against lethal challenge. The extent to which mediator cells accumulated in exudates was found to be governed by the level of their production in responding lymphoid tissue and by the time available for them to migrate into an exudate. An intraperitoneal injection of casein at any stage of infection resulted in a progressive accumulation of mediator cells that continued for 3 days. The accumulation was not caused by continuous entry of cells during the whole of this period, but resulted from division of a limited number of cells that entered during the first 24 h. Accumulation of mediator cells in an exudate was associated with the conversion of a population of dividing cells into a population of nondividing T cells with a relatively short life-span.